ANALISIS PEMANFAATAN PLATFORM MADRASAH SUMBAR PADA MATA PELAJARAN PENDIDIKAN PANCASILA DAN KEWARANEGARAAN DI MAN 1 PADANG PARIAMAN - Mardiah Salbaini; Fetri Yeni J; Nofri Hendri; Mutiara Felicita Amsal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study is motivated by the demand for digitalization in education, which requires teachers and students to adapt to the development of learning technologies. One of the innovations introduced is the Madrasah Sumbar platform, an online system designed to support teaching and learning activities in madrasahs through features such as learning material distribution, automatic attendance, assignments, and online examinations. The purpose of this study is to describe the utilization of the Madrasah Sumbar platform in Civic Education (PPKn) learning, to identify its strengths and weaknesses, and to analyze the challenges faced by teachers and students in its implementation. This research employed a qualitative descriptive approach with data sources including the principal, school operator, Civic Education teachers, and students at MAN 1 Padang Pariaman. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data display, and conclusion drawing. The findings of this study reveal that: (1) the utilization of the Madrasah Sumbar platform has supported the PPKn learning process through uploading materials, providing assignments, conducting examinations, and recording digital attendance; (2) the advantages of the platform include automatic attendance, ease of accessing materials, and an automatic grading system, while its weaknesses are the less interactive display, the absence of a discussion forum, and full dependency on internet connectivity; and (3) the obstacles encountered by teachers and students include limited internet access, manual account creation, and technical issues during examinations.